PENERAPAN ALGORITMA EVEN-RODEH PADA APLIKASI KOMPRESI FILE GAMBAR - Pramadi, Agus Adi; Nasution, Surya Darma; Purba, Bister (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
Some image files are very large in size. So it requires a large memory storage capacity too, this is certainly a lot of costs that must be spent on the storage media. With the existence of a very large image file size in the process of sending image data files can fail because the storage media exceeds the maximum limit. The above problems can be overcome by performing the process of compressing large image files into small sizes or can reduce the bit size contained in each image file thereby saving storage containers and simplifying the process of transferring image files to other storage media. The solution to this problem is how the image file can be compressed in order to speed up the transfer and storage of image files. Image file compression aims to reduce or reduce the size of the file but does not eliminate the information data in it. With the compression technique, the data was initially large so that the size of the data can be reduced so as to save storage allocation space. In this study using the Even-Rodeh Code algorithm, using the method results in very good compression in tramisi data and transfer of image file allocation easier and faster.Keywords: Image File Compression, Event Rode Code Algorithm